2005
DOI: 10.1111/j.1365-2133.2005.06755.x
|View full text |Cite
|
Sign up to set email alerts
|

Circulating CD8+ lymphocytes, white blood cells, and survival in patients with mycosis fungoides

Abstract: The measurement of CD8+ cells and WBC in MF seems to be a promising criterion to predict survival, and possibly to support treatment decisions and inclusion of patients in randomized controlled trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
1
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 32 publications
(34 reference statements)
0
30
1
1
Order By: Relevance
“…9 Low numbers of CD8 ϩ T cells in the dermal infiltrate and/or the blood have also been independently associated with reduced survival. 14,20,21 Managing early-stage (IA-IIA) MF…”
Section: B2mentioning
confidence: 99%
“…9 Low numbers of CD8 ϩ T cells in the dermal infiltrate and/or the blood have also been independently associated with reduced survival. 14,20,21 Managing early-stage (IA-IIA) MF…”
Section: B2mentioning
confidence: 99%
“…[13][14][15][16][17][18][19][20] However, none of these markers is directly associated with the tumor phenotype of the SS cells and they seem to be mere markers of risk or, at best, the result of some deregulated mechanisms. Here we describe, for the first time, the prognostic significance of two antigens directly related to T-cell function, and thus possibly involved in the pathogenesis of SS.…”
Section: Discussionmentioning
confidence: 99%
“…4,5,11,12 Previous studies of prognostic indicators in SS showed that circulating Sézary cell count, high CD4/CD8 ratio, advanced age, high lactate dehydrogenase serum level and a high white blood cell count were associated with an unfavorable outcome. [13][14][15][16][17][18][19][20] Up to now, scanty data have been provided concerning possible associations between the immunophenotype of circulating CD4 + T cells and survival in SS. As for other hematologic malignancies, 21,22 it is important to clarify the prognostic relevance of activation of homing receptors expressed by circulating CD4 + T cells in SS, since these markers might be directly linked to the pathogenesis and outcome of the disorder.…”
Section: Introductionmentioning
confidence: 99%
“…Other prognostic factors, whether laboratory or histopathologically based, have also been identified, such as significant tissue CD30+ expression (suggesting large cell transformation), decreased tissue CD8+ expression, elevated LDH, significant peripheral blood burden of malignant cells, and blood eosinophilia. In the past year, a study showed that decreased peripheral blood CD8 T-cell count (<250 cells/μL) and elevated total leukocyte count (>9000 cells/μL) correlated with worse OS [22].…”
Section: Mycosis Fungoides and Variants/subtypesmentioning
confidence: 99%